Survival of the fritters - Bolton, Ginger (Bolton, Ginger. Deputy Donut mystery., 2018)
Emily Westhill runs the best donut shop in Fallingbrook, Wisconsin, alongside her retired police chief father-in-law and her tabby Deputy Donut. But after murder claims a favorite customer, Emily can't rely on a sidekick to solve the crime--or stay alive.